DESIGN AND MANUFACTORING OF A LABORATORY STAND FOR TESTING ACCELERATED TENSILE CREEP OF PLASTICS ACCORDING TO ASTM D6992 (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The article discusses stages of design and manufacturing of a laboratory stand for accelerated tensile creep of plastics according to ASTM D6992. All components necessary for accurate operation of the laboratory stand will be examined: jaws, deadweight system,loading weights, linear strain measurement system and control, test temperature control and monitoring, test data storage and management. The aim of the article is to create flexible systems that allow the stand to be used for other similar test standards and materials. The main task in the design and manufacturing of the stand is to create reliable equipment with a high accuracy degree, automated loading of a control program, as well asability to store a large volume of data for the purpose of creating a database and comparing test results. The mathematical model for calculating equivalent years is directly integrated for easier processing of experimental results. The stand is designed and manufactured for testing 2 samples simultaneously , which facilitates  comparison of data from different polymer blends.The stand is calibrated according to its three main quantities - linear strain, temperature and deadweights.The calibration results are presented to assess accuracy of the laboratory stand systems. The stand fully meets the requirements defined according to ASTM D6992. The accuracy of the calibrated quantities allows precise calculations of accelerated creep data on a wide range of materials. Design and manufacturing steps may also be used with other standardized and non-standardized creep tensile testing methods of plastics, as well as other laboratory equipment needs with similar systems and goals.